Development of research skills in initial teacher training: case of the Universidad Pedagógica Veracruzana (Mexico), academic year 2022-2023 - González, Gonzalo (2024)
The Universidad Pedagógica Veracruzana (UPV) offers the Bachelor's Degree in Basic Education, which constitutes the initial teacher training. Over eight semesters, students explore topics in educational research through an integrative approach. Considering that the Educational Reform of 2019 in Mexico establishes that teachers' knowledge and skills should be directed towards creating solutions with their communities, the research aimed to understand the knowledge, skills, and educational research interests declared by students in the eighth semester during the academic year 2022-2023 in the Dlegree program at UPV. The adopted methodological approach is quantitative, with a descriptive scope and a non-experimental cross-sectional design. Out of the 115 students who completed the eighth semester at the Xalapa Regional Center during the academic year 2022-2023, this study focused on 95 of them who completed an electronic questionnaire, along with the documentary review of 115 research papers produced by all students in the same semester. The goal was to identify the knowledge, skills, and research interests declared by the students. From this, it was found that the most significant themes in their work were related to teaching and learning techniques in the field of language and communication. Over 60% of the studied population considered having research skills and knowledge. These results provide valuable information to propose support alternatives to strengthen these educational research skills during initial teacher training, thereby improving the perception of educational issues to be addressed.